Management of serum calcium reductions among patients on hemodialysis following cinacalcet initiation†. (2nd August 2015) - Brunelli, Steven M.; Dluzniewski, Paul J.; Cooper, Kerry; Do, Thy P.; Sibbel, Scott; Bradbury, Brian D.
Abstract Purpose Cinacalcet is indicated for treatment of secondary hyperparathyroidism in patients receiving hemodialysis. Cinacalcet reduces serum calcium concentrations by decreasing parathyroid hormone secretion, but the frequency and degree of calcium reduction following cinacalcet initiation, subsequent physician response, and ultimate calcium recovery in clinical practice are not well described. Methods Patients receiving hemodialysis at a large dialysis organization who enrolled in the organization's prescription benefits service and initiated cinacalcet at serum calcium ≥8.4 mg/dL were studied (N = 13 723). Patients were categorized by whether they experienced a reduction in calcium to <8.4 mg/dL and to what level (<7.5, 7.5–7.9, and 8.0–8.3 mg/dL). Baseline characteristics, frequency of subsequent intervention, and calcium recovery were compared. Results Of those who experienced a reduction in calcium to <8.4 mg/dL (n = 6437 [46.9%]), 6.6% had calcium <7.5 mg/dL and 24.5% had calcium 7.5–7.9 mg/dL, while the majority (68.9%) had a level of 8–8.3 mg/dL. Higher baseline parathyroid hormone and alkaline phosphatase were associated with lower resultant calcium. Among patients with calcium reductions, 45.6–63.5% received one or more directed clinical therapeutic responses, including 15.6–28.4% for whom cinacalcet was discontinued; the majority of patients recovered to calcium ≥8.4 mg/dL within 90 days of first detection. Only modest differences in recovery were noted between patients who did and did not receive any therapeutic response and patients who did and did not discontinue cinacalcet. Conclusion Serum calcium reductions following cinacalcet initiation were common; declines <7.5 mg/dL were infrequent. Calcium recovery occurred in the majority of patients, with or without therapeutic intervention. Copyright © 2015 John Wiley & Sons, Ltd.